2020
DOI: 10.1117/1.jbo.25.4.048001
|View full text |Cite
|
Sign up to set email alerts
|

Beyond 2D: effects of photobiomodulation in 3D tissue-like systems

Abstract: Significance: Currently, various scaffolds with immobilized cells are widely used in tissue engineering and regenerative medicine. However, the physiological activity and cell viability in such constructs might be impaired due to a lack of oxygen and nutrients. Photobiomodulation (PBM) is a promising method of preconditioning cells to increase their metabolic activity and to activate proliferation or differentiation. Aim: Investigation of the potential of PBM for stimulation of cell activities in hydrogels. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Three studies were used hydrogels or 3D fibrin [ 37 , 41 , 42 ], associated with PBM, being incorporated into the fibrin matrix endothelial cells [ 41 ], stromal vascular fraction (SVF) and mesenchymal stromal cells (MSCs) isolated from human gingival mucosa [ 37 ]. These studies agree that photobiomodulation combined with fibrin enhances the improvement of results, collaborating in cell and vascular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies were used hydrogels or 3D fibrin [ 37 , 41 , 42 ], associated with PBM, being incorporated into the fibrin matrix endothelial cells [ 41 ], stromal vascular fraction (SVF) and mesenchymal stromal cells (MSCs) isolated from human gingival mucosa [ 37 ]. These studies agree that photobiomodulation combined with fibrin enhances the improvement of results, collaborating in cell and vascular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Such phenotype variety can be caused by the altered mechanical properties of the substrate [ 45 , 46 ]. Moreover, it has been shown that cells need a proper surface patterning for alignment, while relatively soft porous substrates often cause a round cell morphology [ 47 , 48 ]. Therefore, PPCOG performed as an adhesive and porous biomesh, which makes it an excellent model for 3D cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…These semiconductor sources usually have a small area ( ) and LED/LD matrices or integrated optical components may be used to shape its radiation pattern. 100 102 LED and LD matrices are also more efficient for homogeneous irradiation of large areas, but, without special shapers, light intensity from laser devices often has a Gaussian shape with a maximum irradiance at the center and decreased irradiance on the periphery.…”
Section: Photobiomodulation and Scaffolds: Intersection Pointsmentioning
confidence: 99%
“… 161 Both red and NIR PBM stimulate metabolic activity and proliferation of gingival MSC encapsulated in a fibrin hydrogel. 101 It seems that PBM activates cell division in sufficiently soft scaffold systems, such as decellularized dermal matrices and hydrogels. 160 162 …”
Section: Pbm For Tissue Engineering and Regenerative Medicinementioning
confidence: 99%